Feline Comorbidities: Clinical perspective on diabetes mellitus and pancreatitis. Issue 7 (July 2022) - Xenoulis, Panagiotis G; Fracassi, Federico
Practical relevance: Diabetes mellitus (DM) is one of the most common feline endocrine disorders. It has been shown by several studies that DM in cats frequently coexists with pancreatitis. Clinical challenges: It has not been definitively established what the exact pathogenetic association between DM and pancreatitis is in the cat. However, the association between these two conditions is most likely bidirectional, with DM predisposing cats to pancreatitis and vice versa. Diagnosis of pancreatitis in cats with DM is crucial because concurrent pancreatitis commonly leads to difficulties in the management of DM. When pancreatitis is associated with diabetic ketoacidosis (DKA), therapeutic management is even more challenging. Aims: This review focuses on the concurrent presence of DM or DKA and pancreatitis in cats, mainly focusing on their clinical management. Evidence base: Information provided in this review is based on feline-specific clinical research when available. In addition, comparative and human research, as well as clinical experience, has been used to enrich knowledge in areas where feline-specific research is not yet available.